Voice Over Internet Protocol (VoIP) User Location Detection Application - Elsa Sanjaya Putri; Mohammad Fadhli; Martinus Mujur Rose (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
This study aimed to build a Voice Over Internet Protocol (VoIP) User Location Detection Application and address information security for the public if they receive attention from unknown or undesired people. This application displays a map or location of people who communicate with others via mobile phones. The Application Development Methodology used the Iteration Method appeared in the database. Application testing used the black-box testing method, and the test results ran according to the expected function. The final result of this research was a telephone application that functioned by displaying a map on the phone screen of the call’s receiver. Therefore, without being asked, when the recipient picks up the phone, they connect to the map -in case something unwanted happens or when the callers merely want to exchange information with each other.